A Novel Approach for Reliable Communications within Inductive Power Transfer Systems - Sanftl, Benedikt; Pflaum, Felix; Trautmann, Martin; Weigel, Robert; Kölpin, Alexander (Wireless Power Transfer Conference (WPTC), 2016)
This paper presents a novel approach for simultaneous inductive power transfer (IPT) and communication in one system. The communication part is using the coupled pair of coils of the IPT system as transmitting medium. The proposed architecture is usable in new and existing IPT systems with operating frequencies above 100 kHz. The challenge is to enable robust and reliable communication in the noisy environment of the power transfer. High reliability is necessary as it shall transmit sensor data error free. For example, this data link can be used for closed-loop operation of the IPT system. Through its fully digital implementation it can be quickly adapted for various other applications. It will be shown that a reliable communication system with joint power transfer and continuous data transmission over the same pair of coupling coils can be realised. Even during high power transfers it features a robust communication channel with outstanding signal to noise ratio and advantageous error vector magnitude. For proof of concept the key performance values of the proposed communication architecture are measured in a 20 W IPT system.
elib2cris::1512001600,sanftl2016a